Comprehensive Transcriptomic Analysis Identifies Novel Antiviral Factors Against Influenza A Virus Infection - Zhou, Ao; Dong, Xia; Liu, Mengyun; Tang, Bin (Frontiers in Immunology, 2021)
Influenza A virus (IAV) has the higher genetic variation, leading to the poor efficiency of traditional vaccine and antiviral strategies targeting viral proteins. Therefore, developing the broad-spectrum antiviral treatments is particularly important. Host responses to IAV infection provides a promising approach to identify antiviral factors involved in virus infection as potential molecular drug targets. In this study, in order to better illustrate the molecular mechanism of host responses to IAV and develop the broad-spectrum antiviral drugs, we systematically analyzed mRNA expression profiles of host genes in a variety of human cells, including transformed and primary epithelial cells infected with different subtypes of IAV by mining 35 microarray data from GEO database. The transcriptomic results showed that IAV infection resulted in the difference expression of amounts of host genes in all cell types, especially those genes participating in immune defense and antiviral response. In addition, following the criteria of P<0.05 and |logFC|≥1.5, we found that some difference expression genes were overlapped in different cell types under IAV infection via integrative gene network analysis. IFI6, IFIT2, ISG15, HERC5, RSAD2, GBP1, IFIT3, IFITM1, LAMP3, USP18 and CXCL10 might act as key antiviral factors in alveolar basal epithelial cells against IAV infection, while BATF2, CXCL10, IFI44L, IL6 and OAS2 played important roles in airway epithelial cell in response to different subtypes of IAV infection. Additionally, we also revealed that some overlaps (BATF2, IFI44L, IFI44, HERC5, CXCL10, OAS2, IFIT3, USP18, OAS1, IFIT2) were commonly upregulated in human primary epithelial cells infected during high or low pathogenicity IAV. Moreover, there were the similar defence responses activated by IAV infection, including interferon-regulated signalling pathway in different phagocyte types, although the differentially expressed genes in different phagocyte types showed a great difference. Taken together, our findings will better understand the fundamental patterns of molecular responses induced by highly or lowly pathogenic IAV and the overlapped genes upregulated by IAV in different cell types may act as early detection markers or broad-spectrum antiviral targets.